The Perspective of Mashlahah Mursalah on the Implementation of Marriage Counseling for Generation Z at the Ampek Angkek Religious Affairs Office - Nurul 'Izzati; Arsal Arsal (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study is motivated by the skeptical views among Generation Z (Gen Z), who perceive that the marriage counseling conducted by the Office of Religious Affairs (KUA) in Ampek Angkek lacks real social impact (mashlahah) and is often regarded merely as an administrative formality. This study aims to determine the methods and materials used in marriage counseling at KUA Ampek Angkek and to analyze them from the perspective of mashlahah mursalah. Utilizing a descriptive qualitative method with a field research approach, data were gathered through interviews, observations, and documentation with KUA officials and Gen Z informants. Data analysis was conducted systematically through data reduction, data display, and conclusion drawing based on relevant theories. The results indicate that marriage counseling is routinely held using lecture and Q&A methods, covering topics such as marriage jurisprudence (fiqh munakahat), family psychology management, positive law, and local customs. Viewed from the mashlahah mursalah perspective, the substance of the material basically fulfills the elements of benefit to foster a harmonious family (jalb al-mashalih) and prevent the harm of divorce (daf’ al-mafasid). However, the conventional and formal delivery methods are considered less interactive and irrelevant to the communication characteristics of Gen Z, leading to suboptimal absorption of these beneficial values. Therefore, this study recommends that KUA Ampek Angkek innovate its counseling approach by integrating visual-based digital learning media, playing short educational videos, and implementing role-play simulations that are more adaptive to the learning styles of Gen Z.